الحجر بين الشريعة والقانون الجزائري - قريشي عيسى -مراد حمزة (جامعة المسيلة, 2021)
وفي ختام هذا البحث الذي تناولت فيه موضوع الحجر بين الفقه الإسلامي والتشريع الجزائري، نخلص إلى جملة من النتائج نجمعها في ما يلي: 1-أن المشرع الجزائري قد وفق نوعا ما في وضعه لأحكام الحجر بين كل من قانون الأسرة وغيره من القوانين الأخرى التي تناولت أحكامه فنجد: أ- اعتبر المشرع الجزائري في القانون المدني كل من المجنون والمعتوه عديمي الأهلية )المادة 42) والسفيه ناقص الأهلية (المادة 43)، وبالمقابل نص على أن الأشخاص المصابين بالعاهات السابقة – الجنون، العته أو لسفه - إذا ما بلغوا وهم بهذه الحالة أو طرأت عليهم بعد رشدهم يحجر عليهم، وهو ما جاء في المادة 101 من قانون الأسرة. ب- نص المشرع الجزائري على الحجر القانوني في قانون العقوبات من خلال المادتين 09 و09 مكرر، واعتبر أن الشخص المحكوم عليه بعقوبة جنائية يحجر عليه، ونص في الفقرة الثانية من المادة 09 مكرر ق.ع.ج على طريقة إدارة أمواله والتي اعتبرها تتم طبقا للإجراءات المقررة في حالة الحجر القضائي، وبالتالي تطبيق أحكام المواد 101 إلى 108 من ق.أ.ج. ج- اعتبر المشرع الجزائري في قانون الأسرة أن الحجر لا يكون إلا بموجب حكم قضائي (المادة 103)، وبين إجراءات توقيعه في قانون الإجراءات المدنية والإدارية، كما أنه حماية لمصالح المحجور عليه أجاز للقاضي أن يفصل في دعوى الحجر بموجب أمر فنص على إجراءات توقيعه من خلال المواد 481 إلى 489 ق.إ.م.إ. Abstract: At the conclusion of this research, in which I dealt with the subject of the stone between Islamic jurisprudence and Algerian legislation, we conclude a number of results, which we collect in the following: 1- The Algerian legislator has somewhat reconciled in his setting the provisions of the stone between each of the family law and other laws that dealt with its provisions, so we find: A- The Algerian legislator considered in the civil law both the insane and the lunatic to be incompetent (Article 42) and the foolish incompetent (Article 43). After they are mature, they are quarantined, which is what is stated in Article 101 of the Family Code. B - The Algerian legislator stipulated legal interdiction in the Penal Code through Articles 09 and 09 bis, and considered that a person sentenced to a criminal penalty would be placed under interdiction, and stipulated in the second paragraph of Article 09 bis Q.A.C on the method of managing his funds, which he considered to be carried out in accordance with the procedures prescribed in the case of judicial interdiction, and consequently the application of the provisions of Articles 101 to 108 of the A.C.C. C - The Algerian legislator considered in the Family Code that the interdiction is only by virtue of a judicial ruling (Article 103), and the procedures for signing it in the Civil and Administrative Procedures Law, and that it is a protection for the interests of the interdicted, allowed the judge to decide the interdiction lawsuit by virtue of an order stipulating the procedures for signing it from During Articles 481 to 489 BC
Keywords: الحجر - الشريعة -القانون